Unpacking correctional workers' experiences with transgender prisoners in Nova Scotia, Canada. Issue 4 (December 2022) - Johnston, Matthew S; Coulling, Ryan; Ricciardelli, Rosemary
Empirical research on Canadian correctional workers' successes, challenges, and attitudes towards accommodating gender diversity remains limited. Drawing on data garnered from two open-ended survey questions (n = 70) asking correctional workers in the community or institutions about their perspectives on working with trans populations, we explore how correctional workers in Nova Scotia, Canada accommodate or struggle to accommodate gender diversity in carceral settings. We found that respondents are generally mindful of issues pertaining to the safety and security of trans prisoners, usually espouse open-mindedness, and are generally able to work within correctional parameters to accommodate those with a diverse gender identity. Yet some respondents raised concerns and suspicion towards prisoners who present a safety risk to other prisoners and, in their view, may be manipulating human rights policies to cause harm to others. We take up these tensions critically and discuss the scholarly and practical implications of our findings, as well as possible avenues for future research.